Silencing the CSF-1 Axis Using Nanoparticle Encapsulated siRNA Mitigates Viral and Autoimmune Myocarditis - Meyer, Ingmar Sören; Goetzke, Carl Christoph; Kespohl, Meike; Sauter, Martina; Heuser, Arnd; Eckstein, Volker; Vornlocher, Hans-Peter; Anderson, Daniel G.; Haas, Jan; Meder, Benjamin; Katus, Hugo Albert; Klingel, Karin; et al. (Frontiers in Immunology, 2018)
Myocarditis is an inflammatory disease of the heart muscle most commonly caused by viral infection and often maintained by autoimmunity. Virus-induced tissue damage triggers chemokine production and, subsequently, immune cell infiltration with pro-inflammatory and pro-fibrotic cytokine production follows. In patients, the overall inflammatory burden determines the disease outcome. Following the aim to define specific molecules that drive both immunopathology and/or autoimmunity in inflammatory heart disease, here we report on increased expression of colony stimulating factor 1 (CSF-1) in patients with myocarditis. CSF-1 controls monocytes originating from hematopoietic stem cells and subsequent progenitor stages. Both, monocytes and macrophages are centrally involved in mediating tissue damage and fibrotic scarring in the heart. CSF-1 influences monocytes via engagement of CSF-1 receptor, and it is also produced by cells of the mononuclear phagocyte system themselves. Based on this, we sought to modulate the virus-triggered inflammatory response in an experimental model of Coxsackievirus B3-induced myocarditis by silencing the CSF-1 axis in myeloid cells using nanoparticle-encapsulated siRNA. siCSF-1 inverted virus-mediated immunopathology as reflected by lower troponin T levels, a reduction of accumulating myeloid cells in heart tissue and improved cardiac function. Importantly, pathogen control was maintained and the virus was efficiently cleared from heart tissue. Since viral heart disease triggers heart-directed autoimmunity, in a second approach we investigated the influence of CSF-1 upon manifestation of heart tissue inflammation during experimental autoimmune myocarditis (EAM). EAM was induced in Balb/c mice by immunization with a myocarditogenic myosin-heavy chain-derived peptide dissolved in complete Freund's adjuvant. siCSF-1 treatment initiated upon established disease inhibited monocyte infiltration into heart tissue and this suppressed cardiac injury as reflected by diminished cardiac fibrosis and improved cardiac function at later states. Mechanistically, we found that suppression of CSF-1 production arrested both differentiation and maturation of monocytes and their precursors in the bone marrow. In conclusion, during viral and autoimmune myocarditis silencing of the myeloid CSF-1 axis by nanoparticle-encapsulated siRNA is beneficial for preventing inflammatory tissue damage in the heart and preserving cardiac function without compromising innate immunity's critical defense mechanisms.